Aquatic Diptera (Insecta) assemblages in four sympatric Eryngium (Apiaceae) phytotelmata in flowering and senescent times - Campos, Raúl Ernesto (2016)
This study addresses how Diptera assemblages differ in four sympatric phytotelmata. The Eryngium species retain water in their axils forming a phytotelm and this situation leads to the speculation that dipteran assemblages may differ, mainly when the plants begin to grow and retain more water in their axils, and when becoming senescent. Diptera from Eryngium horridum, Eryngium stenophyllum, Eryngium aff. serra and Eryngium elegans were sampled. This study revealed that the Eryngium spp. are used by Diptera differentially and their populations show seasonal changes, with peaks in the autumn. Diptera were represented by immature stages belonging to six aquatic and seven semi-aquatic families. The most important were Chironomidae, Culicidae, Periscelididae and Ceratopogonidae. Two species of Chironomids were the most abundant. Culicidae, Periscelididae and Ceratopogonidae were more selective than Chironomidae. Saprophages were the most abundant where the fine detritus feeders were the dominant group. Periscelididae was the main free-swimming predator.